Clinical, parasitological aspects, and gene detection (Pfk13) of Plasmodium falciparum in children aged 6 to 59 months with uncomplicated malaria in Bolenge, Democratic Republic of the Congo - KILARA KAPENE, Tarcisse; Mpiempie, Thérèse N.; Pholo, Jean Paul M.; Makila, Felicité; Ngale, Mireille; Divengi, Jean Paul N.; Kondani, Mamie A.; Velela, Percy K.; Ilenga, Willems M.; Balu, Constant M.; Woto, Isaac T.; Bongenya, Berry I.; et al. (Orapuh Journal, 2025)
Introduction Malaria, caused mainly by Plasmodium falciparum in sub-Saharan Africa, remains a major public health concern. It typically manifests as persistent fever and high parasitemia. Of particular concern is the emergence of resistance to artemisinin derivatives, the current reference treatment. Such resistance is often linked to mutations in the Pfk13 gene, recognised as a molecular marker for surveillance. However, clinical, parasitological, and Pfk13 gene data on children under five years of age in Bolenge remain insufficient. Purpose To describe the clinical and parasitological profiles and determine the prevalence of the Pfk13 gene in children aged 6–59 months with uncomplicated malaria in Bolenge, DRC. Methods This descriptive cross-sectional study was conducted between April 2021 and September 2022, using blood samples collected on filter paper during previous research on the therapeutic efficacy of antimalarial drugs in Bolenge (2017). The study involved 90 children selected through convenience sampling. DNA was extracted from filter paper samples and analysed via classic PCR for Pfk13 mutations. Children included had fever ≥ 37.5 °C and P. falciparum monoinfection with parasitemia between 2,000 and 200,000 trophozoites/μl. Data were analysed using SPSS v20, with descriptive statistics and 95% confidence intervals reported. Results The mean age was 43.5 months. A total of 85.6% presented with fever ranging from 37.5–39 °C. Mean parasitemia was 25,000 trophozoites/μl. The Pfk13 gene was detected in 50% (n = 45) of samples, producing 800 bp amplicons. Conclusion These results highlight the need to optimise DNA storage and integrate molecular surveillance of Pfk13 into national malaria control policies in Bolenge. Such integration would strengthen the early detection of potential artemisinin resistance and enable the development of targeted therapeutic strategies.